Estimation of Botanical Composition in Mixed Clover–Grass Fields Using Machine Learning-Based Image Analysis - Sun, Sashuang; Liang, Ning; Zuo, Zhiyu; Parsons, David; Morel, Julien; Shi, Jiang; Wang, Zhao; Luo, Letan; Zhao, Lin; Fang, Hui; He, Yong; Zhou, Zhenjiang (Frontiers in Plant Science, 2021)
This study aims to provide an effective image analysis method for clover detection and botanical composition (BC) estimation in clover-grass mixture fields. Three transfer learning methods, namely fine-tuned DeepLab V3+, SegNet, and fully convolutional network-8s (FCN-8s), were utilized to detect clover fractions (on an area basis). The detected clover fraction (CFdetected), together with auxiliary variables, viz. measured clover height (Hclover) and grass height (Hgrass) were used to build multiple linear regression (MLR) and back propagation neural network (BPNN) models for botanical composition estimation. A total of 347 clover-grass images were used to build the estimation model on clover fraction and botanical composition. Of the 347 samples, 226 images were augmented to 994 images for training, 25 were selected for validation, and the remaining 96 samples were used as an independent dataset for testing. Testing results showed that the intersection-over-union (IoU) values based on the DeepLab V3+, SegNet, and FCN-8s were 0.73, 0.57, and 0.60, respectively. The root mean square error (RMSE) values for the three transfer learning methods were 8.5%, 10.6%, and 10.0%, respectively. Subsequently, models based on BPNN and MLR were built to estimate BC, either by using CFdetected only or CFdetected, grass height, and clover height all together. Results showed that BPNN was generally superior to MLR in terms of estimating BC. The BPNN model only using CFdetected had a RMSE of 8.7%. In contrast, the BPNN model using all three variables (CFdetected, Hclover, and Hgrass) as inputs had an RMSE of 6.6%, implying that DeepLab V3+ together with BPNN can provide good estimation of BC, and offer a promising method for improving forage management.